Wikipedia, friend or foe regarding information on diabetic retinopathy? A content analysis in the world’s leading 19 languages - Aguilar-Morales, Kouatzin; Aguirre-Suarez, Gustavo; Bowles, Brigham; Lee, Angel; Lansingh, Van Charles (PloS one, 2021)
To compare the completeness and quality of information about diabetic retinopathy on Wikipedia in the world's leading spoken languages in 2020. An observational, descriptive, cross-sectional study. The information on diabetic retinopathy obtained from the free encyclopedia Wikipedia.sup.® was assessed in languages with one hundred million or more total speakers. The term "diabetic retinopathy" was accessed in the corresponding Wikipedia entry in English, while the "more languages" function gives access to other languages. The information on the sites was collected by three ophthalmologist observers. A database was created with the most important subtopics for the education of patients with diabetic retinopathy in any of its classifications, based on a 25-question survey. The results were stratified on a scale from 0 to 4. A confirming correlation was found in the statistical analysis among the observers. No language achieved the label "excellent"; 2 languages were rated as "fair "; 4 languages qualified as "substandard"; and 7 languages were scored as "poor." No information could be found in five languages. As would be expected, the quality of content is variable across different languages. However, if anyone can edit Wikipedia, health professionals can do so as well to improve the quality and quantity of information for patients.